2017
DOI: 10.1002/pdi.2080
|View full text |Cite
|
Sign up to set email alerts
|

Let's Prevent Diabetes: from idea to implementation

Abstract: The prevention of Type 2 Diabetes Mellitus (T2DM) is a global health care priority. We describe a programme of work, which developed a method for identifying those with Non Diabetic Hyperglycaemia (NDH) (a high risk group in which T2DM is preventable) in primary care and developed and tested a prevention programme suitable for delivery within the NHS. The subsequent implementation of this programme as part of the NHS Diabetes Prevention Programme, which was launched in 2016, is then described. IntroductionThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In 2017, an estimated 425 million people were living with T2D, and this is projected to increase to 629 million by 2030 [ 1 , 2 ]. As T2D is potentially preventable, the implementation of effective strategies to prevent the development of T2D is a priority [ 3 ]. Trials have shown that prevention programmes targeting those with the highest risk [ 4 ] may be effective in delaying the onset of T2D [ 5 9 ] for up to 15 years.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, an estimated 425 million people were living with T2D, and this is projected to increase to 629 million by 2030 [ 1 , 2 ]. As T2D is potentially preventable, the implementation of effective strategies to prevent the development of T2D is a priority [ 3 ]. Trials have shown that prevention programmes targeting those with the highest risk [ 4 ] may be effective in delaying the onset of T2D [ 5 9 ] for up to 15 years.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the IDF Guidelines, diabetes research has been challenged by issues such as low uptake of screening and problems with recruitment to education sessions . Diabetes research has also been criticized for not considering context, erring on the side of focusing on interventions to change individual behaviour, when effectiveness is actually influenced by factors outside an individual's control, including physical environment (access to healthy affordable food, opportunities for activity), psychosocial context (exposure to stressors, mental health and coping strategies) and biological characteristics .…”
Section: Introductionmentioning
confidence: 99%